Economic evaluation for the US of nab-paclitaxel plus gemcitabine versus FOLFIRINOX versus gemcitabine in the treatment of metastatic pancreas cancer. (3rd April 2017) - Gharaibeh, Mahdi; McBride, Ali; Bootman, J. Lyle; Patel, Hitendra; Abraham, Ivo
Abstract: Background: Nab-paclitaxel plus gemcitabine (NAB-P + GEM) and FOLFIRINOX have shown superior efficacy over gemcitabine (GEM) in the treatment of metastatic pancreatic ductal adenocarcinoma (mPDA). Although the incremental clinical benefits are modest, both treatments represent significant advances in the treatment of a high-mortality cancer. In this independent economic evaluation for the US, the aim was to estimate the comparative cost-utility and cost-effectiveness of these three regimens from the payer perspective. Methods: In the absence of a direct treatment comparison in a single clinical trial, the Bucher indirect comparison method was used to estimate the comparative efficacy of each regimen. A Markov model evaluated life years (LY) and quality-adjusted life years (QALY) gained with NAB-P + GEM and FOLFIRINOX over GEM, expressed as incremental cost-effectiveness (ICER) and cost-utility ratios (ICUR). All costs and outcomes were discounted at 3%/year. The impact of parameter uncertainty on the model was assessed by probabilistic sensitivity analyses. Results: NAB-P + GEM was associated with differentials of +0.180 LY and +0.127 QALY gained over GEM at an incremental total cost of 25, 965; yielding an ICER of 144, 096/LY and ICUR of 204, 369/QALY gained. FOLFIRINOX was associated with differentials of +0.368 LY and +0.249 QALY gained over GEM at an incremental total cost of 93, 045; yielding an ICER of 253, 162/LY and ICUR of 372, 813/QALY gained. In indirect comparison, the overall survival hazard ratio (OS HR) for NAB-P + GEM vs FOLFIRINOX was 0.79 (95%CI = 0.59–1.05), indicating no superiority in OS of either regimen. FOLFIRINOX had an ICER of 358, 067/LY and an ICUR of 547, 480/QALY gained over NAB-P + GEM. Tornado diagrams identified variation in the OS HR, but no other parameters, to impact the NAB-P + GEM and FOLFIRINOX ICURs. Conclusions: In the absence of a statistically significant difference in OS between NAB-P + GEM and FOLFIRINOX, this US analysis indicates that the greater economic benefit in terms of cost-savings and incremental cost-effectiveness and cost-utility ratios favors NAB-P + GEM over FOLFIRINOX.